An approach to the variables and their classification scale, through “age” as a study variable - Luis Alberto Corona Martínez; Mercedes Fonseca Hernàndez (Medisur)
The variables’ operationalization constitutes a research action of great methodological importance. This article briefly reviews theoretical aspects about the study variables, to substantiate the greatest usefulness and convenience of declaring, in the research project, the type of scale that will be used to group the data coming from of the units of analysis, instead of the type of variable, as is usually done. This idea takes on an obvious practical meaning when working with quantitative variables.